Labor out-migration and agricultural change in rural China: A systematic review and meta-analysis. (October 2016) - Qin, Hua; Liao, Tim F.
Abstract: The relationships between migration and agriculture represent a key aspect of rural restructuring in China and many other developing countries. Previous research largely generated mixed and incomplete findings on the effects of rural out-migration on agricultural change. Meta-analysis is considered as an important research strategy for comparing and integrating results from individual studies. Using a qualitative comparative analysis (QCA) approach, we conducted a systematic review and meta-analysis of recent case studies of labor out-migration and agricultural change in rural China. The analysis revealed general contextual patterns of migration impacts on agriculture. Migration-induced agricultural change was mainly conditional upon the specific conjunctural configuration of a rural community's economic development level or geographical locality, its land resources and dependence on agriculture, and whether the period under investigation was post-agricultural tax abolition. Overall, this meta-study provides the big picture of the complex migration–agriculture relationships in rural China, which is often missed in smaller-scale case studies. Such synthetic findings are particularly useful for informing evidence-based rural development planning and policy making. Highlights: Migration–agriculture relationships represent a key aspect of rural restructuring. We conducted a meta-analysis of migration and agricultural change in rural China. Our QCA analysis included 20 case studies from 12 selected publications. The analysis revealed general contextual patterns of migration effects on agriculture. The QCA configurations mainly reflected regional and economic development settings.